1982
DOI: 10.3758/bf03213716
|View full text |Cite
|
Sign up to set email alerts
|

Food aversion learning in kangaroo rats: A specialist-generalist comparison

Abstract: Two species of kangaroo rat (Dipodomys), varying in their degree of dietary specialization, were compared in a series of food aversion learning experiments to test the hypothesis that rapid aversion learning is an adaptation of relatively generalist feeders. The more generalist species indeed learned better or more rapidly in certain experiments, but species differences were at least partly a function of the specific test foods. Interpretation of results is complicated by differences between the two species in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…It is possible, for example, that learning of "win-stay" and "win-shift" strategies proceeds at the same rate against different baseline tendencies for spontaneous alternation. Daly, Rauschenberger, and Behrends (1982) recently completed a study that is more closely in line with our proposals. Two species of kangaroo rat (Dipodomys) that varied in their degree of dietary specialization were compared in a series of foodaversion learning studies.…”
Section: A Comparative Approach To the Study Of Association Learningsupporting
confidence: 64%
“…It is possible, for example, that learning of "win-stay" and "win-shift" strategies proceeds at the same rate against different baseline tendencies for spontaneous alternation. Daly, Rauschenberger, and Behrends (1982) recently completed a study that is more closely in line with our proposals. Two species of kangaroo rat (Dipodomys) that varied in their degree of dietary specialization were compared in a series of foodaversion learning studies.…”
Section: A Comparative Approach To the Study Of Association Learningsupporting
confidence: 64%
“…Neophobia, in contrast, varies with stimulus complexity and the degree of deviation from what the organism has experienced before (variation) and the same may apply for exploration, innovation and learning . Several studies ranging from birds to mammals have shown that diet or habitat generalists are less neophobic than diet and habitat specialists supporting the Neophobia Threshold hypothesis stating that experiences made early in life (e.g. number of food types/habitats) are protected by neophobia later in life .…”
Section: Cognitive Adaptations To Stable Environmentsmentioning
confidence: 99%
“…Neophobic animals may encounter and use a narrower range of food types than neophilic ones, and learn less rapidly about cues and rewards Ethology 107, 281Ð293 (2001) Ó 2001 Blackwell Wissenschafts-Verlag, Berlin ISSN 0179±1613 associated with novel situations they face in the ®eld and in the laboratory (Greenberg & Mettke-Homann 2000 1,2 1,2 ). As a consequence, learning dierences predicted from dierences in diet breadth (Rozin & Schull 1988) can be confounded by dierences in willingness to eat new foods (Daly et al 1982).…”
Section: Introductionmentioning
confidence: 99%